DIALOGUE ABOUT THE LIABILITY OF CORPORATE SOCIAL CONCEPTS (CSR) AND MARKETING FOR SOCIAL CAUSES (MCS) INVESTMENT IN THE CONTEXT OF CORPORATE SOCIAL (ISC) - Moraes, Nelson Russo de [UNESP]; Braga Junior, Sergio Silva [UNESP]; Bressan Smith Lourenzani, Ana Elisa [UNESP] (Univ Nove Julho, 2015)
With the evolution of social relations between business organizations and society, especially after the 1980s, a multitude of terminologies comes in addition to propose specific to their applications, causing some understanding of disorders and sometimes its clumsy handling. The following question was the guiding element of the study: How corporate social participation is characterized: social responsibility and marketing?. In order to analyze the practical application of contemporary concepts of social responsibility and marketing, this study presents the theoretical dialogue and empirical analysis about the appropriation of the terms marketing and social responsibility by companies located in a Brazilian city (Bauru/SP). The results show that midsize companies have a strong social responsibility, while social marketing is the predominant profile of companies with headquarters outside the municipality.
Keywords: Social Responsibility; Marketing; Social Marketing; Social Investment; Philanthropy